Analysis of Fracture Behaviour on PLA Specimen with Varied Lattice Structure Density - Mohamad Syazwan Zafwan, Mohamad Suffian; Siti Shuhadah, Shamsul Anuar; Syahiir, Kamil; Marlynna, Sarkawi (The Italian Association of Chemical Engineering, 2025)
Polylactic acid (PLA) is a type of bioplastic that is biodegradable, has lower greenhouse gas (GHG) emissions, and a smaller carbon footprint. It is produced from natural resources, such as biopolymers, and possesses good mechanical properties. Therefore, it is widely used as a material for fast prototyping, particularly in additive manufacturing techniques, such as the Fused Deposition Modelling (FDM). However, additive-manufactured products made from PLA exhibit varying mechanical strength properties when different densities of lattice structures are applied. In this paper, the analysis of fracture mechanics and strength of additively manufactured products made from PLA with varying lattice architectures and densities is conducted. Lattice structures, which are rectilinear and feature complete honeycomb architecture, are chosen in this study. Dogbone-shaped specimens were produced via a 3D printing FDM machine, with each specimen having a varied density of lattice structure. A tensile test was performed on each specimen to analyse its strength and mechanical properties. Analysis of the full honeycomb lattice structure strength has shown that the relationship between the maximum tensile strength and the infill density is not proportional and fluctuates. 40 % infill density possesses the highest maximum tensile strength, and 20 % infill density has the lowest maximum tensile strength. By increasing the infill density of the additive-manufactured product using PLA material, the tensile properties of the specimen have also improved, resulting in a product with enhanced strength.